Diets and environments of late pleistocene pygmy and Columbian mammoths: Isotopic evidence from Southern California - Chance D. Hannold; Yang Wang; Xiaoming Wang; Regan Dunn; Jonathan Hoffman (PLoS ONE, 2026)
Pygmy mammoths ( Mammuthus exilis ) and Columbian mammoths ( Mammuthus columbi ) coexisted on the island of Santarosae (now the Northern Channel Islands of California) until the Late Pleistocene megafaunal extinctions, but the ecology of these mammoths is not yet well explored. In this study, we reconstructed the diets and environments of Late Pleistocene pygmy and Columbian mammoths using stable isotopes in tooth enamel samples from the Northern Channel Islands and Rancho La Brea. The enamel δ 13 C values indicate that these mammoths primarily consumed C 3 vegetation. However, a few individuals consumed significant amounts of C 4 plants, CAM plants, or water-stressed woody C 3 plants. The mean diet-δ 13 C value for mainland mammoths (−24.2 ± 1.4‰) is about 2‰ higher than that of island mammoths (−26.4 ± 1.9‰), suggesting that most mainland mammoths consumed either water-stressed C 3 vegetation, or some C 4 and/or CAM plants. Reconstructed δ 18 O values of paleo-water from the mainland are generally lower than the mean δ 18 O values of modern precipitation in Southern California, suggesting conditions were wetter and/or cooler than today. Reconstructed δ 18 O values of paleo-water from the islands are more similar to modern precipitation. δ 13 C-based estimates of mean annual precipitation range from 159 to 1407 mm/yr on the islands and from 28 to 387 mm/yr on the mainland. However, consumption of small amounts of C 4 and/or CAM plants may have resulted in an underestimation of precipitation for the mainland. Radiometric dating of additional fossils from both localities will help clarify the links between climate change and mammoth evolution and extinction in the region.